Serosurvey of anti-Leptospira sp and anti-Toxoplasma gondii antibodies in capybaras and collared and white-lipped peccaries - Ullmann, Leila Sabrina [UNESP]; Gravinatti, Mara Lucia; Yamatogi, Ricardo Seiti [UNESP]; Santos, Leonilda Correa dos; Moraes, Wanderlei de; Cubas, Zalmir Silvino; Camossi, Lucilene Granuzzio [UNESP]; Barros Filho, Ivan Roque de; Langoni, Helio [UNESP]; Costa Vieira, Rafael Felipe da; Biondo, Alexander Welker (Soc Brasileira Medicina Tropical, 2017)
Introduction: Brazilian native species are reemerging as increasingly free-ranging populations. Methods: Sera from 31 capybaras (Hydrochoerus hydrochaeris) and 28 peccaries (Pecari tajacu and Tayassu pecari) were tested for anti-Leptospira and anti-Toxoplasma gondii antibodies using microscopic seroagglutination test. Results: Nineteen percent of free-ranging and 10.0% of captive capybaras, along with 31.8% of collared peccaries, were seropositive for T. gondii. None was seropositive for Leptospira sp. Conclusions: The present findings indicated low risk of disease, particularly among capybaras and white-lipped peccaries; however, active surveillance programs are important for monitoring wildlife health and public health once they are in public parks around cities.
Keywords: Leptospirosis; Toxoplasmosis; Captive; Free-ranging